The economic adjustment programme for Greece - Second review – autumn 2010 (Luxembourg, 2010)
"A joint Commission/ECB/IMF mission met with the Greek authorities in Athens on 15-22 November 2010. The mission assessed compliance by Greece with the terms and conditions of the second review under the economic adjustment programme and updated conditionality for the next reviews.